Accupuncture treatment for chronic traumatic knee synovitis in athletes: 42 cases of clinical experience - He, C. J.; Wu, Z. Y. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Synovitis of the knee is common in sports heavily involving the lower limbs such as basketball, volleyball, handball, gymnastics, and weightlifting. The characteristics may be represented by a long course of illness, frequent reoccurrence of injury and aggravation following movement which causes a performance decline. Treatment for the condition is complex and this paper reviews the results of acupuncture intervention in the treatment of this problem. Methods The analysis used evidence from 42 cases of knee synovitis which occurred between March 1994 and August 2002, during a period when the author was the doctor consulting to the Chinese fencing team and other national teams. in handball, free fighting. and outpatients. The 42 cases included 17 males and 25 females between the age of 13 and 28 years. The length of injury ranged from one-month to 3 years. Twenty-eight cases had confirmed trauma history and others had a history of over training in the lower limbs as a function of repeated part squat positions, taking off, changeable runs, heavy loaded squats, over runs and jumps on hard surfaces. Diagnosis of the condition required a history of trauma or fatigue. It was a,lso associated with the following symptoms: knee swelling, effusion with aggravation after training or competition, with mitigation after rest, knee pain or discomfort pain, joint space tenderness, a positive test for joint effusion induced swelling, more fluid than normal, and a positive floating patella test which was positive during a lunge exercise. The treatment consisted of pump treatment for a positive floating patella test result. Reduced or cessation of training on the injured legs, and exercises prescribed to strengthen the quadriceps muscles. Acupuncture treatment was also prescribed and the shortest course of treatment was 14 days, and the longest was two months. Results The condition was successfully treated in 31 cases following acupuncture treatment, with another 11 cases showing improvement. Discussion Chronic traumatic knee synovitis occurred as a function of unsuitable training methods. Acupuncture treatment proved successful in the treatment of this condition, together with a reduction in training and rehabilitation exercises.